Bimolecular proximity of a ruthenium complex and methylene blue within an anionic porous coordination cage for enhancing photocatalytic activity. Issue 12 (15th February 2019) - Fang, Yu; Xiao, Zhifeng; Kirchon, Angelo; Li, Jialuo; Jin, Fangying; Togo, Tatsuo; Zhang, Liangliang; Zhu, Chengfeng; Zhou, Hong-Cai
Abstract : An anionic coordination cage encapsulates the catalyst and the substrate within its cavity, circumvent the charge repulsion, thus promotes the activity in the photocatalysis. Abstract : The charge repulsion between a catalyst and substrate will significantly reduce the contact occurring between them, resulting in low reactivity. Herein, we report an anionic porous coordination cage that is capable of encapsulating both a cationic catalyst and cationic substrate in its cavity at the same time. After encapsulating the [Ru(bpy)3 ] 2+ Cl2 (bpy = bipyridine) catalyst, the cage/catalyst composite serves as an active heterogeneous catalyst for the photo-degradation of methylene blue (MB). The highly negatively charged cavity of PCC-2 allows for the sequential encapsulation of the cationic methylene blue substrate and the Ru catalyst, which in turn significantly shortens the distance between them, yielding an increased possibility of MB degradation. Moreover, the encapsulated Ru catalyst dramatically outperformed its homogeneous counterpart in terms of overall degradation performance and recyclability.